2013
DOI: 10.1080/02699931.2013.832152
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal inventiveness: The ability to create different reappraisals of critical situations

Abstract: In this article, we propose a new ability approach to reappraisal that focuses on individual differences in the ability to spontaneously generate different reappraisals for critical situations. Adopting concepts from the realms of creativity and divergent thinking, we developed the Reappraisal Inventiveness Test (RIT) to measure a person's fluency and flexibility in inventing as many categorically different reappraisals for an anger-eliciting situation as possible within a limited period of time. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
162
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(171 citation statements)
references
References 49 publications
6
162
1
2
Order By: Relevance
“…A student sample was chosen, because the used version of the behavioral test of the capacity for generating cognitive reappraisals (Weber et al 2014) had been tailored for a student population (the items include negative experiences that students can easily imagine happening to them). Individuals who reported having a neuropsychiatric disease or using psychoactive medication were not included in the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A student sample was chosen, because the used version of the behavioral test of the capacity for generating cognitive reappraisals (Weber et al 2014) had been tailored for a student population (the items include negative experiences that students can easily imagine happening to them). Individuals who reported having a neuropsychiatric disease or using psychoactive medication were not included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…While widely used in psychology (e.g., intelligence tests) and several medical disciplines such as neurology (e.g., motor performance tests) and psychiatry (e.g., neuropsychological testing), the use of maximum performance measures, capturing what individuals are theoretically capable of doing, is a novel concept in psychotherapy research. The theoretical capacity for generating cognitive reappraisals can be regarded a direct prerequisite for the ability to effectively implement cognitive reappraisal in everyday life (Weber et al 2014). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, exposing participants to four sessions of reappraisal training increased their ability to reduce their negative feelings when viewing negative pictures as well as their experience of stress in their lives [19]. Other studies have found no association between self-reported use of reappraisal in everyday life and reappraisal ability as measured in laboratory tasks [20,21]. However, we have been unable to find research directly assessing how the cognitive costs of reappraisal vary for individuals with more or less frequent use of reappraisal.…”
Section: Introductionmentioning
confidence: 99%